Fluorescent imaging of antigen released by a skin-invading helminth reveals differential uptake and activation profiles by antigen presenting cells. - Ross A Paveley; Sarah A Aynsley; Peter C Cook; Joseph D Turner; Adrian P Mountford (Public Library of Science (PLoS), 2009)
Infection of the mammalian host by the parasitic helminth Schistosoma mansoni is accompanied by the release of excretory/secretory molecules (ES) from cercariae which aid penetration of the skin. These ES molecules are potent stimulants of innate immune cells leading to activation of acquired immunity. At present however, it is not known which cells take up parasite antigen, nor its intracellular fate. Here, we develop a technique to label live infectious cercariae which permits the imaging of released antigens into macrophages (MPhi) and dendritic cells (DCs) both in vitro and in vivo. The amine reactive tracer CFDA-SE was used to efficiently label the acetabular gland contents of cercariae which are released upon skin penetration. These ES products, termed '0-3hRP', were phagocytosed by MHC-II(+) cells in a Ca(+) and actin-dependent manner. Imaging of a labelled cercaria as it penetrates the host skin over 2 hours reveals the progressive release of ES material. Recovery of cells from the skin shows that CFDA-SE labelled ES was initially (3 hrs) taken up by Gr1(+)MHC-II(-) neutrophils, followed (24 hrs) by skin-derived F4/80(+)MHC-II(lo) MPhi and CD11c(+) MHC-II(hi) DC. Subsequently (48 hrs), MPhi and DC positive for CFDA-SE were detected in the skin-draining lymph nodes reflecting the time taken for antigen-laden cells to reach sites of immune priming. Comparison of in vitro-derived MPhi and DC revealed that MPhi were slower to process 0-3hRP, released higher quantities of IL-10, and expressed a greater quantity of arginase-1 transcript. Combined, our observations on differential uptake of cercarial ES by MPhi and DC suggest the development of a dynamic but ultimately balanced response that can be potentially pushed towards immune priming (via DC) or immune regulation (via MPhi).